The Role of Entrepreneurial Marketing in Improving Marketing Performance in Batik Smes In Pekalongan Regency - Danang Satrio; Adela Syaefira (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study was to examine and analyze the effect of entrepreneurial marketing on marketing performance. The subjects of this study were 61 Batik SMEs in Pekalongan Regency. Entrepreneurial marketing is measured by opportunity focused, proactiveness, customer intensity, risk-taking, resource leveraging, value creation, innovation. The large number of business people in Pekalongan Regency makes each actor must read the opportunities and determine what to do so that they can survive among the many other actors, especially for those who are just starting their business. Appropriate market orientation and determination of the right market strategy that can be carried out by business people, especially in the batik sector will have an impact on the profits that will be obtained by the perpetrators. In addition, actors are also able to innovate products so that they are able to provide uniqueness to the products offered, which can have an impact on marketing performance so that what the actors get is a profit. This research uses multiple linear regression analysis method. The results of this study prove and conclude that: (1) opportunity focused has a significant positive effect on marketing performance; (2) proactiveness has no significant negative effect on marketing performance; (3) customer intensity has a significant positive effect on marketing performance; (4) risk-taking has no significant negative effect on marketing performance; (5) resource leveraging has a significant positive effect on marketing performance; (6) value creation has no significant negative effect on marketing performance; and (7) innovation has a significant positive effect on marketing performance.